Marketing Strategies and Challenges in Conventional Travel Agency : Case Study: Classic Tour & Travel - Surayyal Hizmi; Ida Ayu Yadnya Sari Dewi Utami Pidada; Baiq Lerin Oksantiya Andini; Anas Pattaray (Politeknik Pariwisata Bali, 2025)
Competition in Indonesia's tourism industry is increasingly competitive, especially with the dominance of Online Travel Agent (OTA) platforms that are shifting the role of conventional travel agents. This research aims to analyse the marketing strategies and challenges faced by Classic Tour & Travel as a conventional travel agent amidst the fast-changing digital landscape. The research method used is a qualitative case study approach with data collection techniques through in-depth interviews with key informants. The results showed that Classic Tour & Travel implements various marketing strategies, including direct selling, participation in travel marts, limited digital marketing, as well as the use of conventional promotional media such as brochures and pamphlets. The main constraints faced include limitations in technology adoption, non-digital-ready human resources, and competitive pressure from OTAs with more efficient cost structures. This study confirms the importance of strengthening relational strategies, tourism product innovation, and contextual and adaptive marketing approaches for the survival of conventional travel agents. The findings are relevant for industry players, academics, and policy makers in designing strategies to strengthen the competitiveness of the locally-based tourism sector.